Growth Performance and Carcass Characteristics of Broiler Chickens Fed Diets Containing Differently Processed Finger Millet Supplemented with Enzyme - Edache, David O.; John, Samuel O.; Edache, Stephen E.; Emmanuel, Dongtem; Edache, John A. (International Journal of Poultry Science, 2025)
Objectives: The present study was conducted to assess the performance and carcass characteristics of broiler chickens fed diets containing differently processed finger millet meal supplemented with enzymes. Materials and Methods: A total of 150 two-week-old broiler chicks of mixed sexes were randomly allocated to one of four diets in a completely randomized block design. The broiler chicks were allocated one of four diets containing either 0 (Control), uncrushed, roughly crushed, or finely crushed finger millet. The starter diets were isonitrogenous (23% CP) but varied in energy levels from 2,710.00 (Diet A) to 2,726.60 kcal/kg ME (for diets B, C and D respectively). The finisher diet was also isonitrogenous (21% CP) and fed to the birds for 21 days. A total of 37 broiler birds were divided into four groups, each receiving a finisher diet containing 0 (control), uncrushed, roughly crushed and finely crushed finger millet, all (except for control) supplemented with enzyme for 3 weeks. Each diet was replicated thrice with 12 birds each. Some replicates had 13 birds each. Feed and water were made available ad libitum. Results: Feed intake was significantly lower (p